2012
DOI: 10.1200/jco.2011.38.1103
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of 2-[18F]Fluorodeoxyglucose Positron Emission Tomography in the Assessment of Regional Nodal Spread of Disease in Patients With Breast Cancer: An Ontario Clinical Oncology Group Study

Abstract: FDG-PET is not sufficiently sensitive to detect positive axillary lymph nodes, nor is it sufficiently specific to appropriately identify distant metastases. However, the very high positive predictive value (96%) suggests that PET when positive is indicative of disease in axillary nodes, which may influence surgical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 23 publications
4
45
0
1
Order By: Relevance
“…Biopsy or additional imaging and follow-ups 37 96 83 74 FDG PET/CT could not be recommended as a primary diagnostic procedure Groheux et al [16] 2011 70 SLNB or US-FNA 63 91 63 91 FDG PET/CT might impact cancer management in small portions of patients Koolen et al [3] 2012 290 SLNB or US-FNA 82 92 98 53 FDG PET/CT could be recommended as a standard staging procedure Pritchard et al [18] that FDG PET/CT contributes to pretreatment staging and therapy planning, upstaging substantial proportion of patients to the high risk group, thereby potentially changing prognosis and possibly implicating postoperative irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biopsy or additional imaging and follow-ups 37 96 83 74 FDG PET/CT could not be recommended as a primary diagnostic procedure Groheux et al [16] 2011 70 SLNB or US-FNA 63 91 63 91 FDG PET/CT might impact cancer management in small portions of patients Koolen et al [3] 2012 290 SLNB or US-FNA 82 92 98 53 FDG PET/CT could be recommended as a standard staging procedure Pritchard et al [18] that FDG PET/CT contributes to pretreatment staging and therapy planning, upstaging substantial proportion of patients to the high risk group, thereby potentially changing prognosis and possibly implicating postoperative irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recently published Ontario Clinical Oncology Group Study with 325 patient enrollments and ALND or SLNB as the gold standard following FDG PET/CT, the sensitivity, specificity, positive predictive value and negative predictive value were 23.7%, 99.6%, 95.8% and 75.4% [18] . Using logistic regression, primary tumor size was predictive for prevalence of the nodal lesion and for PET sensitivity.…”
Section: Nodesmentioning
confidence: 99%
“…Several groups have demonstrated that, in most cases, FDG-PET or PET/CT has a low sensitivity (range 24-82 %) but a high specificity (range 80-100 %) and high positive predictive value (PPV) of more than 80 % [24][25][26][27][28][29][30][31][32][33]. In a review of 472 patients examined using FDG-PET/CT, the pooled sensitivity was relatively low (60 %) but the pooled specificity was very high (97 %) [34].…”
Section: Axillary Lymph Node Stagingmentioning
confidence: 99%
“…To determine whether 18 F-FDG PET is useful for evaluating axillary lymph node involvement and detecting distant metastasis in women with primary breast cancer, 325 women diagnosed with operable breast cancer were screened by Pritchard et al [27] . SLNs were found in 312 (96%) of the 325 women.…”
Section: Comparison Of 18 F-fdg Pet (Pet/ct) and Slnb For Detecting Rmentioning
confidence: 99%